Fuzzy Logic Analysis of Parameters of Dimples of Ductile Tearing on the Digital Image of Fracture Surface. (2017) - Konovalenko, Igor; Maruschak, Pavlo; Chausov, Mykola; Prentkovskis, Olegas
Abstract: An automated method for analyzing shapes and sizes of dimples resulting from fracture of titanium alloy VT 23, which can be used in technical diagnostics systems, is proposed. The developed approaches to the analysis of images of fracture surfaces obtained from scanning microscope allow highlighting the components of the objects under study, performing their morphological analysis, and evaluating the mutual relationship between them. The proposed algorithm has a self-processing feature for the identification of the objects sought in the images of fracture surfaces, because it does not need to be adapted to images of different types, and does not require any individual adjustment of parameters.